Constructing TiO2 decorated Bi2WO6 architectures with enhanced visible-light-driven photocatalytic activity. (11th May 2017) - Yang, Zhiyuan; Chen, Lu; Yang, Yun; Wang, Junjie; Huang, Yongkui; Liu, Xiaoxia; Yang, Shuijin
Abstract: TiO2 nanoparticles modified Bi2 WO6 photocatalysts were prepared via a facile hydrothermal process. The photocatalytic activity of as-prepared TiO2 /Bi2 WO6 composites was investigated sufficiently by the photodegradation of rhodamine B (RhB), tetracycline hydrochloride (TC) and ciprofloxacin (CIP). The TiO2 /Bi2 WO6 composites, in which the molar ratio of TiO2 to Bi2 WO6 is 1:1, exhibited optimum photocatalytic activity, which is found to increase by about 2.4 times more than that of pristine Bi2 WO6 for the photodegradation of TC. The enhanced photocatalytic activity may be attributed to the higher surface area and the highly efficient charge separation between Bi2 WO6 nanosheets and TiO2 nanoparticles. The mechanism of the photocatalysts is investigated by the determination of reactive species in the photocatalytic reactions, the photoluminescence measurement and photoelectrochemical analyses.